Case Report: Mucopolysaccharidosis Type I Treatment With α-L-Iduronidase Replacement Therapy - Li, Ying; Liu, Deyun; Yu, Yue (Frontiers in Pediatrics, 2022)
Mucopolysaccharidosis is a rare disease and can be divided into seven different subtypes, according to the affected enzyme. Mucopolysaccharidosis type I, the first subtype discovered and reported, mainly affects the in vivo storage of degraded sugar. The current treatment methods are symptomatic therapy, enzyme replacement therapy, and allogeneic hematopoietic stem cell transplantation. In China, the enzyme for the treatment of mucopolysaccharidosis type I was approved in June 2020. We report a case of an 18-month-old Chinese boy with mucopolysaccharidosis type I who received enzyme replacement therapy with concentrated laronidase solution. This is the second case of the disease in China, and the first case of a child under two years of age. Following the therapy, urine mucopolysaccharide particles levels were significantly lower, and the patient’s symptoms improved. The medical records of Chinese patients who have been treated with enzyme replacement therapy for mucopolysaccharidosis type I also showed similar results. This case demonstrated that enzyme replacement therapy is a safe and effective treatment for patients with mucopolysaccharidosis type I.